Analisis Faktor - Faktor yang Mempengaruhi Pelaporan Kewajiban Perpajakan UMKM di Kota Kupang dan Dampaknya terhadap Kepatuhan Pajak - Antonius M.L. Uran; Leopold M. T. Dawu; Antonius Y.W. Timuneno (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to the economic development of a country, contributing significantly to job creation, poverty alleviation, and the overall growth of the economy. In Indonesia, including Kupang City, MSMEs are considered a key pillar of the national economy. Despite their economic importance, MSMEs face challenges in fulfilling their tax obligations, with many failing to report taxes in accordance with the law. This non-compliance not only affects tax revenue collection but also hinders the effectiveness of the tax system. This study aimed to identify the factors influencing MSME tax reporting obligations in Kupang City by analyzing the roles of knowledge, understanding, awareness, and tax sanctions. Using a quantitative survey method, the research gathered data from MSMEs registered at the Kupang Tax Office (KPP Pratama). The findings revealed that knowledge, awareness, and tax sanctions have a significant impact on MSMEs' compliance with tax reporting obligations. In particular, knowledge and awareness were found to increase MSMEs' understanding of their responsibilities, motivating them to fulfill their tax obligations. On the other hand, tax understanding, despite being important, did not have a significant direct effect on compliance, which may indicate that practical experience and exposure to tax-related practices play a more crucial role. Moreover, when analyzed simultaneously, all four variables—knowledge, understanding, awareness, and tax sanctions—had a significant impact on MSMEs' tax reporting obligations. These results highlight the importance of targeted interventions, such as comprehensive tax education and regular outreach programs. By offering training sessions, mentoring, and practical workshops, tax authorities can better engage with MSMEs and improve their tax compliance rates.